PENGARUH INVESTASI ASING (FDI), KONSUMSI RUMAH TANGGA, PENGELUARAN PEMERINTAH TERHADAP PEREKONOMIAN INDONESIA - Iin Varlina; Syamsul Amar (Universitas Negeri Padang, 2019)
This study aims to find out how the influence of Foreign Direct Investment (FDI), household concumption, government expenditure of the Indonesian economy. The data used are secondary data in the form of time series from 1983 to 2017, with documentation data collection techniques and library studies obtained from relevant institutions and agencies. The variables used are Indonesian Economy (Y), Foreign Direct Investment (FDI) (X1), household consumption (X2), government expenditure (X3). The research methods used are: (1) Ordinary Last Square (OLS), (2) Classical Assumption Test, (3) T Test and (4) F Test. The results of the study show that (1) Foreign Direct Investment has a positive and significant effect on the economy Indonesia. (2) household consumption has a positive and significant effect on the economy Indonesia. (3) Government Expenditiure has a positive and significant effect on the economy Indonesia.